Aspects of institutional religiosity and/or (non-) credibility of european social survey in Montenegro - Bakrač, Vladimir (Sociološki pregled, 2024)
Using data from the European Social Survey (ESS) from 2018/2019 and 2020/2021, the author investigates the contemporary religious structure in Montenegro, using the variables included in the survey: religious identification, self-assessment of religiosity, attendance at religious services, and prayer. The comparison involves all three confessions in Montenegro: Orthodox, Roman Catholics, and believers of the Islamic religious community. The main goal of the research is to determine whether there has been a shift in religiosity and whether there is an emphasized distance in the religiosity of the three confessions in this country. Moreover, the goal is to get an insight into the current situation regarding religiosity in Montenegro. The working hypothesis is that there is a current stabilization of the religious structure in Montenegro and a discrepancy between religious and confessional declarations and religious practices. Hereupon, we analyse the dimensions of religiosity with regard to basic socio-demographic characteristics and political orientations. The results have shown that there is no significant discrepancy in sex structure. The connection between dimensions of religiosity and “right-wing” political orientation is also registered.